Analisis Keberlanjutan Usaha Tani di Desa Songan A (Studi Pada Masyarakat Petani di Desa Songan, Kintamani, Bangli) - Ni Wayan Mila Ayuni; Made Ary Meitriana (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research was conducted to analyze the status and attributes of farming sustainability in Songan A Village, Kintamani District, Bangli Regency. There are three dimensions of sustainability that will be used to measure the status of farming sustainability in Songan Village, namely the ecological dimension, the economic dimension and the social dimension. The sampling technique in this study was Probability Sampling-Simple Random Sampling. The sample calculation used the Slovin formula to obtain a sample of 97 people. The sustainability analysis method used in this study was. The results of this study using MDS analysis, namely the sustainability index value for the ecological dimension of 68.04 or "quite sustainable", the sustainability index value for the economic dimension of 75.12 or "very sustainable", the sustainability index value for the social dimension of 58.65 or "quite sustainable", and the overall sustainability index of farming in Songan Village is 67.27 "quite sustainable", then there are 5 sensitive attributes that affect the sustainability of farming in Songan Village, for the ecological dimension the sensitive attributes are the level of fertilizer use and the type of fertilizer used, for the economic dimension the attributes that affect sustainability are farmer income and land ownership status, while for the social dimension the attributes that affect sustainability are family participation.